48=-3(4r-3)+3

Simple and best practice solution for 48=-3(4r-3)+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 48=-3(4r-3)+3 equation:


Simplifying
48 = -3(4r + -3) + 3

Reorder the terms:
48 = -3(-3 + 4r) + 3
48 = (-3 * -3 + 4r * -3) + 3
48 = (9 + -12r) + 3

Reorder the terms:
48 = 9 + 3 + -12r

Combine like terms: 9 + 3 = 12
48 = 12 + -12r

Solving
48 = 12 + -12r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '12r' to each side of the equation.
48 + 12r = 12 + -12r + 12r

Combine like terms: -12r + 12r = 0
48 + 12r = 12 + 0
48 + 12r = 12

Add '-48' to each side of the equation.
48 + -48 + 12r = 12 + -48

Combine like terms: 48 + -48 = 0
0 + 12r = 12 + -48
12r = 12 + -48

Combine like terms: 12 + -48 = -36
12r = -36

Divide each side by '12'.
r = -3

Simplifying
r = -3

See similar equations:

| −1/5(x−4)=−2 | | y+4x+1=2y+4x+4 | | 3(6+1)=4(b-5) | | 3*(2x-9)=5*(x-4) | | -9.6v+5.6=-1.6-2.4v | | 1/3x4x15 | | 5x-1=4x-8 | | 4x+8=5x+6 | | -4(4-4p)=48 | | 4n+2-6n+7= | | 3(c-4)=-6 | | 25-(7-2x)=5x | | x^2=-2ln(x+2) | | 44-y=177 | | c-9/-4=-2 | | 2sin^2x+2cos^2x= | | Y=2x^2-4-3 | | 4.7+.91= | | 4[2x-(x+5)]=6(x-9) | | 5=u+30a | | 6(x+12)=-47 | | 1.2h+15=0.8h+28 | | 4.2-1/20x=1/4x | | 7y+28x=21 | | 0.25(x+2)=0.75(3x-4) | | [(2/3)^x]^2 | | 1/18:2 | | 1/9X1/2 | | 3/x=12/24 | | 40(t)=-16t^2+40o | | 2y+7-4y= | | 64/56=x/7 |

Equations solver categories